1993
DOI: 10.1159/000108718
|View full text |Cite
|
Sign up to set email alerts
|

Unrecognized Warning Leak in Ruptured Intracranial Aneurysm

Abstract: Early detection of the warning symptoms of subarachnoid haemorrhage (SAH) may be an effective way to achieve a significant reduction of morbidity and mortality. The present study is part of a survey of all cases of SAH observed in 16 neurosurgical and in 8 neurological departments in Italy between June 1985 and June 1986. Out of 619 patients, 364 cases with aneurysm confirmed by angiography and a detailed clinical history were evaluated. Of these, 308 patients were operated. Warning symptoms were present in 74… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Patients having a warning leak before an aneurysmal SAH had a worse overall outcome than those without a warning leak, even though the difference in outcome was not statistically significant. The adverse prognostic effects of the warning leak reported by other authors 12,16,32,34 are confirmed by our study. However, in a study by Juvela, 14 the presence of a warning leak was found to have no impact on outcome or on the occurrence of complications after the major rupture.…”
Section: Impact Of a Warning Leak On Outcomesupporting
confidence: 92%
See 1 more Smart Citation
“…Patients having a warning leak before an aneurysmal SAH had a worse overall outcome than those without a warning leak, even though the difference in outcome was not statistically significant. The adverse prognostic effects of the warning leak reported by other authors 12,16,32,34 are confirmed by our study. However, in a study by Juvela, 14 the presence of a warning leak was found to have no impact on outcome or on the occurrence of complications after the major rupture.…”
Section: Impact Of a Warning Leak On Outcomesupporting
confidence: 92%
“…The reported incidence of warning signs in SAH patients ranges from 13.5% to 60%. 2,5,6,12,14,16,21,24,28,30,[32][33][34][35] Papers in which high rates are reported include, in addition to headache, less specific symptoms such as purely somatic symptoms and transient neurological dysfunction without headache as a premonition of the SAH. 21,34 In the present study we focused on patients with a history of having experienced a generalized or localized headache with an acute onset.…”
Section: Discussionmentioning
confidence: 99%